Implementasi Metode Klasikal Untuk Meningkatkan Kemampuan Belajar PAI Pada Siswa Di SMP Ulul Albab - Abdullah Zaini (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
The Classical Method is a program of SMP Ulul Albab which aims to improve the ability to learn PAI with a good and correct level of understanding. This study aims to determine how the implementation of classical methods in improving PAI learning ability in Ulul Albab Junior High School students. Researchers conducted research at SMP Ulul Albab because of the environment that is full day school and prioritizes religious understanding accompanied by direct practice. Researchers used a descriptive qualitative approach in this study. The results of this study include several things: 1) The implementation of classical methods in improving the learning ability of Islamic religious education (PAI) in students of SMP Ulul Albab can be carried out comprehensively, especially in fiqh-based learning. 2) The application of the classical method is the act of using material, theory, or method simultaneously. 3) Evaluation of learning in the implementation of classical methods can be carried out by practice-based assessment and direct observation in a non-test manner by the teacher.